2015
DOI: 10.1097/scs.0000000000001890
|View full text |Cite
|
Sign up to set email alerts
|

Finite-Element Analysis of a New Designed Miniplate which is Used via Intraoral Approach to the Mandible Angle Fracture

Abstract: The mandible is the largest facial bone as well as the most commonly fractured bone in the maxillofacial region. Despite numerous studies conducted to identify optimal treatment modalities and plates configurations for intraoral and transoral approaches, no definitive conclusion has been reached. This study used finite element analysis (FEA) to assess 4 scenarios for treatment of an angle fracture (6-hole noncompression miniplate; 6-hole single plate/Champy's technique, 3D strut plate; 2 parallel 4-hole noncom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…The rate of incidence seems to be low, but it leads to overwhelming outcomes such as malunion, non-union, paresthesia, osteomyelitis and prolonged functional and nutritional disturbances [3]. On the other hand, the mandible is the most common broken bone by cause of facial injuries with the ratio of 23–97% [4]. The insertion of implants to the weakend mandibular bone decreases the strength of the bone and may lead to fractures either during or after implant placement [5].…”
Section: Introductionmentioning
confidence: 99%
“…The rate of incidence seems to be low, but it leads to overwhelming outcomes such as malunion, non-union, paresthesia, osteomyelitis and prolonged functional and nutritional disturbances [3]. On the other hand, the mandible is the most common broken bone by cause of facial injuries with the ratio of 23–97% [4]. The insertion of implants to the weakend mandibular bone decreases the strength of the bone and may lead to fractures either during or after implant placement [5].…”
Section: Introductionmentioning
confidence: 99%
“…Authors further confirmed its stability in a 3D finite element study and concluded that NDM can be a useful alternative to other modalities in the treatment of noncomminuted and minimally displaced angle fractures and tensile forces when compared to conventional plates. [ 31 ]…”
Section: Discussionmentioning
confidence: 99%
“…The new plate was assessed using both an experimental study and a finite element analysis and showed promising results regarding resistance to lateral displacement, vertical compressive, and tensile forces. [17,18] Nevertheless, no previous clinical have been conducted on this new plate.…”
Section: Introductionmentioning
confidence: 99%